The Role of MSMEs in Realizing the Sustainable Development Goals (SDGs) - Judijanto, Loso; Hendra, Joni; Islam, Azmi Muhammad (West Science Business and Management, 2025)
This study explores the pivotal role of Micro, Small, and Medium Enterprises (MSMEs) in advancing the Sustainable Development Goals (SDGs) through a systematic literature review of 25 documents sourced from the Scopus database. The analysis highlights MSMEs as drivers of economic growth, social inclusion, and environmental sustainability. Key findings include their contributions to job creation, innovation, and local community development, alongside increasing adoption of sustainable practices such as energy efficiency and waste reduction. However, challenges persist, including limited access to finance, resources, and green technologies. This study underscores the need for supportive ecosystems, capacity-building programs, and targeted policy interventions to maximize MSMEs' contributions to the SDGs. It concludes that fostering collaboration among stakeholders and addressing structural barriers can unlock the full potential of MSMEs in achieving sustainable development.